Proximate composition, minerals, tannins, phytates and cooking quality of commercial cowpea cultivars - Oliveira, Adolfo M. C. de; Jean, Abdias; Damasceno-Silva, Kaesel J.; Moreira-Araújo, Regilda S. dos R.; Franco, Luis J. D.; Rocha, Maurisrael de M. (FapUNIFESP, 2023)
Cowpea is a socioeconomically important legume in the Northeast region of Brazil, and the most grown and consumed type of bean, representing the main source of low-cost vegetable protein for rural and urban populations in this region. The objective of this work was to characterize the proximate composition, minerals, tannins, phytic acid, and cooking quality of whole grains of cowpea from the commercial cultivars BRS Aracê, BRS Inhuma, and BRS Xiquexique. Grain samples of the cultivars were ground in a zirconium ball mill and the flour was used for analysis. The proximate composition was carried out according to the AOAC methodology. The minerals were determined by nitro-perchloric digestion and reading in a flame atomic absorption spectrophotometer. The anti-nutritional factors tannins and phytic acid were determined by extraction and reading in a spectrophotometer. Cooking quality was assessed using an electric pressure cooker and then a Mattson cooker. A completely randomized experimental design was used, with three treatments (cultivars) and three replications. The data were subjected to analysis of variance and the means were compared by the Tukey's test (p<0.05). The cowpea cultivars showed significant differences (p<0.05) for most characteristics evaluated and were similar in terms of ash, lipids, total dietary fiber, and most macrominerals. The results showed that grains of the cultivars BRS Aracê and BRS Xiquexique are excellent sources of dietary fiber, proteins, and minerals and present high cooking quality, while grains of the cultivar BRS Inhuma stood out regarding carbohydrates, soluble dietary fibers, total energetic value, and low levels of factors, anti-nutritional tannins and phytic acid.